Analisis Jaminan Kematian Terhadap Ahli Waris BPJS Ketenagakerjaan Menurut Perspektif Asuransi Syariah (Studi Kasus BPJS Ketenagakerjaan Cabang Medan) - Sundari, Anggi; ., Yusrizal; ., Atika (CV. ITTC INDONESIA, 2023)
BPJS Employment is a state program that aims to provide guaranteed social protection for all Indonesian workers. Death Benefit (JKM) is a social security program implemented nationally based on social insurance principles with the aim of providing death benefits paid to the heirs of participants who die. Fulfilling worldly needs is an obligation. However, fulfilling the world's needs to achieve these needs can be done by protecting yourself, but still following Islamic law. This research aims to find out how the implementation of providing death insurance for the heirs of BPJS Employment Medan Branch according to the Sharia Insurance Perspective. This research uses a qualitative descriptive analysis method. Collecting research data through observation and interviews. The informants for this research are the Head of BPJS Employment Services, Medan Branch Office and the beneficiaries of the Death Insurance Program. The results of the research show that the implementation of providing death insurance to heirs has not been effectively implemented because the death compensation funds to heirs are late so that the death compensation cannot be felt during the death procession starting from the burial of the body to the prayer for the souls from the 7th day, even 40th day soul prayer. This is due to the heirs' lack of understanding in implementing the death insurance program and the application or processing of death insurance application documents requires too many requirements so that getting the death insurance benefits takes a long time. The non-payment of participants' death insurance claims for months by BPJS Employment has three strong indications of maladministration, namely protracted delays, non-compliance and unprofessionalism. Maladministration is behavior or acts against the law and ethics in the public service administration process. The forms of maladministration are procedural deviations, discriminatory actions, abuse of authority, including negligence or neglect of legal obligations, requests for rewards, and others. In the implementation of providing death insurance to heirs by BPJS Employment Medan Branch, it is not in accordance with sharia insurance principles, there is the occurrence of chance which has an impact on the element of maysir (gambling), there is an element of usury fadhl (excess between what is received and what is paid), including fines for lateness.